2021
DOI: 10.21037/atm-20-6781
|View full text |Cite
|
Sign up to set email alerts
|

Clinical application and accuracy analysis of 3D printing guide plate based on polylactic acid in mandible reconstruction with fibula flap

Abstract: Background: Due to the special anatomy morphology and physiological function of the mandible, it has always become a challenge to accurately reconstruct the mandibular defect in maxillofacial surgery. Digital three dimensions (3D) printing surgical guide, as the effective method for individual and accurate surgery, is a hotspot of clinical research at present. In this study, 3D printing PLA surgical guide plate was applied to reconstruct the mandibular defect with fibula flap, its clinical effect and accuracy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…In recent year, 3D printing guide plate has been widely applied in reconstructive surgery for its improvement of personalization, accuracy, and safety of the operation. 28,29 Wu et al 30 reported the use of percutaneous needle guide plate can perform safe and individualized tumor biopsy of acetabulum. It was also used in tumor resection and reconstruction in the field of thoracic surgery, which promoted surgeons' understanding of thoracic wall tumor location, morphology, and invasion range.…”
Section: Discussionmentioning
confidence: 99%
“…In recent year, 3D printing guide plate has been widely applied in reconstructive surgery for its improvement of personalization, accuracy, and safety of the operation. 28,29 Wu et al 30 reported the use of percutaneous needle guide plate can perform safe and individualized tumor biopsy of acetabulum. It was also used in tumor resection and reconstruction in the field of thoracic surgery, which promoted surgeons' understanding of thoracic wall tumor location, morphology, and invasion range.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to operative and ischemic time gains attributable to CAD/CAM, CAMR has enabled more complex surgeries [ 95 ] with a high degree of accuracy in mandibular reconstruction compared to preoperative virtual models [ 93 , 96 ], with a mean error as low as 1 mm (range 0.4–2.46 mm) reported by Tarsitano et al [ 97 ]. A systematic review of subjective cosmetic (e.g., facial appearance, aesthetic/social activity satisfaction) and functional (e.g., regular diet, intelligible speech) outcomes by Powecharoen et al likewise favors CAMR over CFMR [ 94 ].…”
Section: Discipline Specific Applicationsmentioning
confidence: 99%
“…The choice of material is crucial in 3D printing for medical applications. Commonly used materials include the following: Polylactic acid (PLA): Biodegradable and safe for human contact, often used for temporary implants or surgical guides [ 25 ]. Resins: Used in SLA printing, these offer high detail but are generally less durable than other materials [ 26 ].…”
Section: Main Textmentioning
confidence: 99%